Defense Response in Brazilian Honey Bees (Apis mellifera scutellata × spp.) Is Underpinned by Complex Patterns of Admixture. (29th June 2020) - Harpur, Brock A; Kadri, Samir M; Orsi, Ricardo O; Whitfield, Charles W; Zayed, Amro
Abstract: In 1957, an invasive and highly defensive honey bee began to spread across Brazil. In the previous year, Brazilian researchers hoped to produce a subtropical-adapted honey bee by crossing local commercial honey bees (of European origin) with a South African honey bee subspecies ( Apis mellifera scutellata ; an A-lineage honey bee subspecies). The resulting cross—African hybrid honey bees (AHBs)—escaped from their enclosure and spread through the Americas. Today, AHB is the most common honey bee from Northern Argentina to the Southern United States. AHBs are much more likely to sting nest intruders than managed European-derived honey bee colonies. Previous studies have explored how genetic variation contributes to differences in defense response between European-derived honey bee and AHB. Although this work demonstrated very strong genetic effects on defense response, they have yet to pinpoint which genes influence variation in defense response within AHBs, specifically. We quantified defense response for 116 colonies in Brazil and performed pooled sequencing on the most phenotypically divergent samples. We identified 65 loci containing 322 genes that were significantly associated with defense response. Loci were strongly associated with metabolic function, consistent with previous functional genomic analyses of this phenotype. Additionally, defense-associated loci had nonrandom and unexpected patterns of admixture. Defense response was not simply the product of more A-lineage honey bee ancestry as previously assumed, but rather an interaction between A-lineage and European alleles. Our results suggest that a combination of A-lineage and European alleles play roles in defensive behavior in AHBs.